Behavioural ratings of self-regulatory mechanisms and driving behaviour after an acquired brain injury. (December 2014) - Rike, Per-Ola; Ulleberg, Pål; Schultheis, Maria T.; Lundqvist, Anna; Schanke, Anne-Kristine
Abstract Objective: To explore whether measurements of self-regulatory mechanisms and cognition predict driving behaviour after an acquired brain injury (ABI). Design: Consecutive follow-up study. Participants: At baseline participants included 77 persons with stroke and 32 persons with a traumatic brain injury (TBI), all of whom completed a multidisciplinary driving assessment (MDA). A follow-up cohort of 34 persons that succeeded the MDA was included. Baseline measurements: Neuropsychological tests and measurements of self-regulatory mechanisms (BRIEF-A and UPPS Impulsive Behaviour Scale), driving behaviour (DBQ) and pre-injury driving characteristics (mileage, compensatory driving strategies and accident rates). Follow-up measurements: Post-injury driving characteristics were collected by mailed questionnaires from the participants who succeeded the MDA. Methods: A MDA, which included a medical examination, neuropsychological testing and an on-road driving test, was considered in the decision for or against granting a driver's license. Self-regulatory mechanisms and driving behaviour were examined for research purposes only. Results: At baseline, self-regulatory mechanisms were significantly associated to aberrant driving behaviour, but not with neuropsychological data or with the outcome of the on-road driving test. Aspects of self-regulation were associated to driving behaviour at follow-up. Conclusion: It is recommended that self-regulatory measurements should regularly be considered in the driving assessments after ABI.